Firmwide Versus Establishment-Specific Labor Market Practices - Kaplan, David S.; Pierce, Brooks (The Review of Economics and Statistics, 2005)
We construct a novel data set matching occupational data from separate establishments to the establishments' corporate parents, in order to study labor market links across establishments within diverse firms. We find substantial wage components common to all establishments within firms, even after netting out industry and occupation effects. However, employment changes are localized to establishments. The data suggest that internal labor markets of multiestablishment firms are linked throughout their entire organizations, but that establishment-level demand shocks do not permeate the firm.